A bad case of stripes - Shannon, David, 1959- (New York : Blue Sky Press, 1998)
In order to ensure her popularity, Camilla Cream always does what is expected, until the day arrives when she no longer recognizes herself.
AD 540
Accelerated Reader AR
Keywords: Popularity -- Juvenile fiction; Individuality -- Juvenile fiction; Popularity -- Fiction; Individuality -- Fiction; Physicians -- Fiction